PENGARUH PEMERIKSAAN PAJAK DAN PENAGIHAN PAJAK TERHADAP KEPATUHAN WAJIB PAJAK BADAN DENGAN DIGITALISASI ADMINISTRASI SEBAGAI VARIABEL MODERATING (STUDI KASUS KPP MEDAN TIMUR) - Sahra, Maidina; Sari, Maya; Lesmana, Sukma (Worksheet : Jurnal Akuntansi, 2025)
This study aims to analyze the effect of Tax Auditing and Tax Collection on Corporate Taxpayer Compliance, with Digitalization of Administration as a moderating variable at KPP Medan Timur. This study is a quantitative associative research with a path analysis approach using SmartPLS 4 software. A total of 80 questionnaires were used in this study. The results show that Tax Auditing has a positive and significant effect on Corporate Taxpayer Compliance. Tax Collection also has a positive and significant effect on Corporate Taxpayer Compliance. Digitalization of Administration acts as a moderating variable that strengthens the relationship between Tax Auditing and Corporate Taxpayer Compliance, as well as strengthens the effect of Tax Collection on Corporate Taxpayer Compliance. These findings support the theory of technology and innovation, which indicates that the application of technology can enhance the effectiveness of control and compliance.